Teaching competences: diagnosis and innovative activities for development in a distance education model. - Concepción Domínguez Garrido; Genoveva del Carmen Leví Orta; Antonio Medina Rivilla; Eduardo Ramos Méndez (Universitat Politècnica de València, 2014)
This work is the result of a research developed in collaboration with academic experts from five countries (Argentina, Colombia, Ecuador, Mexico and Spain), designed to identify and select a map of relevant teaching competences to improve theaching performance of university teachers in the context of the EHEA. The study is based on analysis of a mixed questionnaire with structured questions and open narratives, completed by a sample of 90 teachers from the UNED. The results show the high value that reaches the map of the twelve competences selected. Using factor analysis and cluster analysis, we can identify two main axes on which all the twelve competences are organized: one, includes the competences of institutional belonging, innovation and research, and the other, includes assessment, tutoring, motivation, planning, professional identity, media integration, methodology and communication; playing a different role the interculturality competence. The ranking of importance derived from the survey placed on the top: planning, methodology, communication and motivation, while less prominent places are occupied by interculturality, institutional belonging and media integration. The corresponding part to the open questions were analyzed with content analysis techniques, predominating the concepts of media integration, professional identity and planning while competences showing less intensity in the narratives are innovation and interculturality.